A Dairy Industry Information Cooperative Service System Based on a Production Process Ontology - Yong XU; Fang-qu NIU; Luke Bergmann; Zhi-qiang WANG; Jian WANG (Journal of Integrative Agriculture, 2012)
Agricultural information cooperative services (AICS) are now becoming an important aspect of agriculture informatization. This study offers an ontological conception of the agricultural production process, establishing operational divisions corresponding to both the stages and the fundamental information requirements of the dairy industry production process in China, yielding a process ontology for the dairy industry as well as a business chain model. A framework for a dairy industry information cooperative service system was established, with service functions realized in a prototype system. The resulting agricultural process ontology built on the basis of biological characteristics has advantages as a classification standard for agricultural information; whereas the business chain model based on this agricultural process ontology allows for an effective distribution of agricultural information cooperative services. This study outlines a concept and demonstrates a prototype of a cooperative service capable of integrating diverse online agricultural information relevant to the dairy industry in China.